A Journey of Trials and Hopes of Individuals with Orofacial Clefts - Ignacio, Edleigh Ian; Logmao, Bea Isabel; Revaño, Karla Mae; Yumul, Sherland Grace (Journal of Interdisciplinary Perspectives, 2025)
Orofacial clefts, including conditions such as cleft lip and palate, represent much more than mere congenital conditions—they signify a profound journey characterized by visible and invisible challenges that extend beyond medical treatment into psychological and social realms. This study explores the lived experiences of individuals with orofacial clefts, highlighting their past and present struggles and aspirations. A review of existing literature reveals the multifaceted challenges these individuals face, including persistent stigma, discrimination, and issues related to self-esteem, all exacerbated by financial burdens and social isolation. To address these matters, this research employs a qualitative-narrative design, utilizing semi- structured interviews with three married female participants aged 31 to 60 from the SOCCSKSARGEN region, specifically General Santos City and Alabel in Sarangani, selected through purposive sampling. The data were analyzed using Bingham and Witkowsky’s (2022) five-phase approach, combining inductive and deductive methods to derive meaningful insights. The findings highlight the urgent need for supportive environments and inclusive policies to empower individuals, enhance well-being, and provide comprehensive support for their emotional, social, and psychological needs.